No Bull Here, Please: Ethical Demands and Expectations of Audiences. (February 2023) - Sinclair, Christine; O'Toole, John
This article is based on a 2007 conference presentation that used Research-Based Theater (RbT) to identify and articulate the ethical questions facing playmakers and audiences, not to provide answers, but to challenge the participants to address them. The authors pose issues of purpose, power, ownership, permission, and audience participation, addressing ethical problems of RbT for performers, audiences, and informants. In the second part of the article, the authors refer readers to the literature to further explore how these issues have been addressed in a range of contexts worldwide . . . and the further questions they raise.